The South African monetary policy and inflation targeting as a nominal anchor: Does the monetary policy become more effective? - Umar, Mohammed; Dahalan, Jauhari; Azman Aziz, Mukhriz Izraf (Inderscience Enterprises Ltd., 2016)
This study investigates whether the South African inflation-targeting (IT) framework has performed the role of the nominal anchor and the process through which the monetary authority determines its instrument in the economy. The study employs generalised method of moments (GMM) estimators. The results of the post-IT adoption and full sample periods are characterised by forward-looking IT rule. Furthermore, the paper uses the augmented monetary policy rule to identify the factors that determine the monetary policy instrument for South Africa. The results confirm that the South African monetary economy practised full-fledged IT principle immediately after the adoption of the IT framework and the monetary policy rule serves as a nominal anchor for the economy. The policy implication is that for South Africa to continue keeping inflation to the required single-digit target, the Reserve Bank should further strengthen the IT framework adopted in the economy.